Amalan kepemimpinan guru di sekolah menengah zon timur Semenajung Malaysia - Harun, Azhar; Basri, Ramli; Lope Pihie, Zaidatol Akmaliah; Asimiran, Soaib (Faculty of Education, University of Malaya, 2016)
The Malaysian Education Development Blueprint (PPPM) through the 5th shift (teachers and school principals) to creating a culture of professional excellence based on colleagues in the 3rd wave (2021-2025). Based on this shift, a study on teacher leadership practices open to sharing leadership among teachers as a new form of leadership that should be explored. Therefore, the main objective of this study was to determine the level of each teacher leadership dimension and, to determine the mean deffrences of teachers leadership practices in High Perfomance Schools (SBT) and non SBT The study used a survey method through a questionnaire Teacher Leadership School Survey (TLSS) by Katzenmeyer and Moller (2001). The respondents consisted of 400 respondents among secondary school teachers in the eastern zone of Peninsular Malaysia. Descriptive and inferential statistics were used to analyze study data. The findings show that a dimension positive environment has the highest mean value. This indicates a positive environment that supports the practice of leadership among teachers. On the whole practice of teacher leadership is located at a high level (M = 4.13, SD = .51) in secondary schools. There was, there was no significant difference is obtained referring to the category of school SBT and non-SBT. The study provides added value to drive KPM/JPN/PPD/school to strengthen leadership at all levels. Based on the role of the Institute of Teacher Education, which serves to provide teacher training, the study suggests that these institutions can provide training modules that provide early exposure to prospective teachers about teacher leadership education to produce future leadership quality and effective in line with the aspirations of 2013 - 2025.